Research on Foreign Air-to-Air Missiles’ Development in 2020 - Ren Miao, Li Hao, Liu Jingjing, Wen Lin (Editorial Office of Aero Weaponry, 2021)
This paper gives a full description of development of foreign air-to-air missiles in 2020. It presents the latest advancement of AIM-9X, AIM-120, MSDM, Gunslinger, Longshot, innovative long-range air-to-air missile, IRIS-T, MICA, Meteor, Russian air-to-air missile, Astra BVRAAM. In the end, the paper summarizes the new development features of air-to-air missiles.